2014
DOI: 10.2319/051314-345.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of skeletal anchoraged Forsus FRD using miniplates inserted on mandibular symphysis: A new approach for the treatment of Class II malocclusion

Abstract: Objective: To evaluate the skeletal, dentoalveolar, and soft tissue effects of the Forsus Fatigue Resistant Device (FRD) appliance with miniplate anchorage for the treatment of skeletal Class II malocclusion. Material and Methods: The prospective clinical study group included 17 patients (11 girls and 6 boys; mean age 12.96 6 1.23 years) with Class II malocclusion due to mandibular retrusion and treated with skeletal anchoraged Forsus FRD. After 0.019 3 0.025-inch stainless steel archwire was inserted and cinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
60
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 21 publications
(37 reference statements)
14
60
1
3
Order By: Relevance
“…In accordance with our results, Unal et al 12 and Celikoglu et al 13 also reported significant mandibular posterior rotation with a skeletally anchored Forsus appliance. In contrast, Aslan et al 11 reported nonsignificant changes in the mandibular plane angle with miniscrew-supported and conventional Forsus appliances.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In accordance with our results, Unal et al 12 and Celikoglu et al 13 also reported significant mandibular posterior rotation with a skeletally anchored Forsus appliance. In contrast, Aslan et al 11 reported nonsignificant changes in the mandibular plane angle with miniscrew-supported and conventional Forsus appliances.…”
Section: Discussionsupporting
confidence: 82%
“…Our results were in accordance with previous studies that have reported similar findings with Forsus appliances. 3,[6][7][8][9][12][13][14]16,17 In contrast, several studies have reported that the Forsus FRD had no significant effect on maxillary growth. 2,5,10,11,18 The effects of the Forsus FRD on mandibular growth were investigated by SNB and Co-Gn measurements.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations